M13 Bacteriophage-Assisted Synergistic Optical Enhancement of Perovskite Quantum Dots - Vanna Chrismas Silalahi; Il Hyun Lee; Minjun Kim; Yudong Jang; Donghan Lee; Jong-Min Lee; Vasanthan Devaraj; Jin-Woo Oh (Applied Sciences, 2023)
Bacteriophages demonstrate a remarkable ability to adhere to host surfaces, thus improving their chances of reproduction. These viral entities demonstrate extreme interface properties through their highly specific and periodic peptide receptors, surpassing any manmade surface in terms of variability and adhesiveness. This intriguing quality has led to investigations into biohybrid nanostructures, wherein bacteriophages are combined with inorganic substances. Among them, cesium lead halide (CsPbI3) perovskite quantum dots (PQDs) are promising emissive materials, with their optical characteristics being vital for the advancement of light-emitting and optoelectronic apparatuses. In this study, we explored the integration of M13 bacteriophages (phages) with CsPbI3 PQDs. Our observations indicated that the photoluminescence of CsPbI3 + M13 phage was amplified 7.7-fold compared to pure CsPbI3, the lifetime of the quantum dots extended from 40.47 ns to 53.32 ns and enhanced the stability. Simulations and experimental results both demonstrate the significant role of M13 bacteriophages in achieving enhanced optical properties for PQDs. These findings confirm the significant contribution of M13 phages to enhancing the optical attributes in PQDs, laying the groundwork for innovative optoelectronic applications.